The Teasing Effect: An Underappreciated Benefit of Creating and Resolving an Uncertainty. (August 2018) - Ruan, Bowen; Hsee, Christopher K.; Lu, Zoe Y.
Seven studies covering diverse contexts show an underappreciated benefit of teasing in information acquisition: first creating and then resolving an uncertainty can generate a net positive experience, yet laypeople do not seek out this process. For example, trivia readers report better hedonic experiences if they are first teased with some missing information and then given that information than if they receive all the information at the same time; however, when given a choice, readers prefer to receive all information at the same time. The authors further show that teasing is hedonically beneficial because uncertainty engenders curiosity and thereby builds a potential for a positive experience, whereas uncertainty resolution satisfies the curiosity and thereby realizes that potential. This research yields practical implications by demonstrating that imbuing an ad with an uncertainty creation–resolution process improves the viewer's attitude toward and increases the viewer's willingness to try the advertised product.